Distribution network reconfiguration utilizing the particle swarm optimization algorithm and exhaustive search methods - Siregar, Yulianta; Jaya Tambun, Tomi Saputra; Panjaitan, Sihar Parlinggoman; Tanjung, Kasmir; Yana, Syiska (Bulletin of Electrical Engineering and Informatics, 2024)
The load level for each period in the distribution network can be considered non-identical due to the increasing demand for loads and the bigger distribution network. The main problem in the transmission and distribution network system is power losses and voltage profiles, affecting the quality of service and operating costs. This study compares the reconfiguration of the network using exhaustive search techniques and particle swarm optimization (PSO) algorithms on the IEEE 33 bus distribution network system. The study’s results compare the study of power flow before and after network reconfiguration, which is a decrease in the value of power losses from 202.7 kW to 139.6 kW. Then voltage profile improved from 91.309% to 93.782%. The simulation results also found that this reconfiguration can improve the system voltage profile, which initially contained 21 buses outside the standard limits of IEEE Std 1159-1995 to 7 buses.